Klinički biohemijski značaj ekspresije STAT6, ERG i miR-647 u raku prostate: povezanost sa agresivnošću tumora i prognozom pacijenta: STAT6, ERG, and miR-647 in Prostate Cancer - Hong, Xin; Zhao, Lin; Wang, Tian; Yang, Xiaobing; Hao, Changzhen (Journal of Medical Biochemistry, 2026)
Background: Reliable molecular indicators that can facilitate early detection and prognosis prediction in prostate cancer are still insufficient. Although Transcription 6 (STAT6), ERG, and microRNA-647 (miR-647) have recently been recognized as key participants in tumor-related signaling pathways, their specific biochemical functions in the context of prostate cancer have yet to be clearly defined. This study evaluated the expression profiles of STAT6 mRNA, ERG mRNA, and miR-647 in prostate cancer tissue and explored their associations with clinicopathological features and patient outcomes.Methods: Surgical specimens were obtained from 70 patients, including both prostate cancer tissues and their corresponding adjacent non-tumorous counterparts. Quantitative real-time PCR (qPCR) was used to measure STAT6 mRNA, ERG mRNA, and miR-647 expression. The relationships between biomarker expression and clinical parameters—including age, tumor diameter, lymph node involvement, T stage, and pathological differentiation—were examined. Overall survival (OS) and progression-free survival (PFS) were evaluated using Kaplan–Meier curves with log-rank comparisons, while Spearman correlation analysis was employed to determine the associations among the examined molecular markers.Results: Levels of STAT6 mRNA, ERG mRNA, and miR-647 were markedly higher in prostate cancer specimens than in the paired non-tumorous tissues (P